Eficiência Energética em Edifícios - Escola Artística Soares dos Reis - Daniel João Macedo Pinhel (2018)
In a context of great global economic development and exponential increase in resources and energy consumption, it is imperative to develop consistent work in matter of efficient management of energy resources. The massive use of fossil, non-renewable resources puts unbearable pressure on the environment. The urban centers, more precisely buildings, are places of great potential of consumption and cost reduction, since many of them have high energetic requirements. Thus, the application of energy efficiency measures, including the exploitation of energy production technologies through renewable natural resources, is highly advantageous. The generalization of these measures is fundamental for sustainable development. The present work will focus on a specific category of buildings, which are the schools, having as a practical case study the Secondary Artistic School of Soares dos Reis (EASR). Characteristically, schools have large energy needs for their operation. The EASR is no exception, and due to fact that is an art's school (it contains factories with different machines and equipment), it certainly has higher energy consumption compared to other schools. The school's current conditions were evaluated in several key areas for energy efficiency. Thus, the tariffs and the quality of energy supply to the school were analysed, as well as the systems of: lighting, HVAC and photovoltaic production. After all necessary information collected and proper characterization, the possibility of optimizing and cost reducing of each of the previously mentioned aspects was studied. For each analysis, the economic and implementation studies were made, then the resulting changes are proposed.